2008
DOI: 10.1007/s10811-007-9307-z
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of nutrient removal and inhibitory effect of Ulva clathrata on Vibrio anguillarum 65

Abstract: To investigate the ecological effect of macroalgae on de-eutrophication and depuration of mariculture seawater, the variation of dissolved inorganic nitrogen (DIN) and phosphate (DIP), the amount of Vibrio anguillarum, and total heterotrophic bacteria in Ulva clathrata culture, as well as on the algal surface, were investigated by artificially adding nutrients and V. anguillarum strain 65 from February to April 2006. The results indicated that U. clathrata not only had strong DIN and DIP removal capacities, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…Finally, macroalgae can excrete allelopathic substances and inhibit phytoplankton growth. Production and excretion of allelochemicals by Ulva is an effective defence strategy against other phototrophic organisms competing for light and nutrients like phytoplankton and epiphytes (Wang et al 2007a), and against pathogens (Lu et al 2008). It has been found that green-tide forming algae, particularly Ulvales, produce allelopathic effects with release of toxic substances for several microalgae (Nelson et al 2003), including harmful algal blooms (Jin and Dong 2003;Wang et al 2007a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, macroalgae can excrete allelopathic substances and inhibit phytoplankton growth. Production and excretion of allelochemicals by Ulva is an effective defence strategy against other phototrophic organisms competing for light and nutrients like phytoplankton and epiphytes (Wang et al 2007a), and against pathogens (Lu et al 2008). It has been found that green-tide forming algae, particularly Ulvales, produce allelopathic effects with release of toxic substances for several microalgae (Nelson et al 2003), including harmful algal blooms (Jin and Dong 2003;Wang et al 2007a, b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that U. clathrata can have high growth rates and yields under wide ranges of temperature, salinity and pH, even growing without inorganic carbon supplementation and with low water exchange (Moll and Deikman 1995). Although large-scale cultivation of U. clathrata has been maintained for food and feed grade use (Moll and Leon 2007), studies on the potential use of the species in integrated aquaculture systems are scarce (Lu et al 2008). This paper aims to evaluate growth, biofiltering efficiency, nutrient uptake and assimilation rates of U. clathrata, cultivated under outdoor conditions within aquaculture waste water from a semi-intensive shrimp farm, located off the south coast of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the second mechanism described above involving complex intercellular interactions, there was no direct inhibition of fish pathogens by phytoplankton, in contrast to other findings [39], [40]. As there was no difference in the viabilities of V. anguillarum between ESM and NCF (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The second one, and more complex, involves a direct interaction between phytoplankton and microbes such as phytoplankton and pathogenic bacteria, probiotic bacteria and pathogenic bacteria, and phytoplanktonprobiotic bacteria and pathogenic bacteria. Regarding the first mechanism, competition for entry of nutrients, the abundance of the Roseobacter clade in the coastal sea is correlated with the release of organic substances from natural phytoplankton blooms such as dimethylsulfoniopropionate (DMSP) and amino acids [105,106]. In turn N. oculata may also excrete some substances similar to DMSP or amino acids that support more optimally bacterial growth of the clade [94].…”
Section: Chemical Signals In Bacteria-microalgae Biofilmsmentioning
confidence: 99%